2022
DOI: 10.3390/ma15113952
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preheating Temperature on Geometry and Mechanical Properties of Laser Cladding-Based Stellite 6/WC Coating

Abstract: The effect of 60Si2Mn substrate preheating on the forming quality and mechanical properties of cobalt-based tungsten carbide composite coating was investigated. Substrate preheating was divided into four classes (room temperature, 150 °C, 250 °C, and 350 °C). The morphology, microstructure, and distribution of elements of the coating were analyzed using a two-color laser handheld 3D scanner, a scanning electron microscope (SEM), and an energy dispersive X-ray spectrometer (EDX), respectively. The hardness and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Notably, when the substrate preheating temperatures were set at 200 • C and 300 • C, the abraded Fe/TiC composite coating displayed relatively smooth surfaces with only minor grooves and isolated pits, suggestive of light wear primarily attributable to slight abrasive action. Consequently, the judicious preheating of the substrate contributes to the enhanced wear resistance of the composite coating, primarily ascribed to the self-lubricating effect of preheating [25].…”
Section: Wear Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Notably, when the substrate preheating temperatures were set at 200 • C and 300 • C, the abraded Fe/TiC composite coating displayed relatively smooth surfaces with only minor grooves and isolated pits, suggestive of light wear primarily attributable to slight abrasive action. Consequently, the judicious preheating of the substrate contributes to the enhanced wear resistance of the composite coating, primarily ascribed to the self-lubricating effect of preheating [25].…”
Section: Wear Resistancementioning
confidence: 99%
“…Conversely, preheating the substrate to 1050 • C yielded a crack-free cladding layer. Wu [25] employed a substrate preheating-assisted laser cladding technique to deposit Stellite 6/WC coating onto the surface of 60Si2Mn steel. The investigation revealed that the introduction of substrate preheating at 350 • C resulted in the formation of diverse structures within the laser cladding layer, characterized by lumps, petals, and flower-like precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Laser cladding process parameters, including laser power, scanning speed, spot size, powder feed rate and standoff distance directly influence the properties of the cladding. These parameters control factors such as heat input, solidification rate, dilution, and microstructure formation, which ultimately impact the properties of the cladding layer [20,21]. Melting of the coating materials is done using a laser beam in laser cladding method.…”
Section: Process Parameters Of Lasermentioning
confidence: 99%
“…Laser cladding technology is characterized by quick heating and cooling, small thermal deformation of substrate material, low dilution rate, a good metallurgical bond formed between cladding and substrate materials, etc. It also has advantages such as short processing time, flexible operation, and high accuracy [2,3], so it was used to prepare the high performance coating on the surface of Q235. At present, the commonly used coating powders for laser cladding include cobalt-based alloys [4], iron-based alloys [5], and nickel-based alloys [6].…”
Section: Introductionmentioning
confidence: 99%